A Case of Gorlin-Goltz Syndrome Presented with Psychiatric Features. (10th March 2014) - Mufaddel, Amir; AlSabousi, Mouza; Salih, Badr; AlHassani, Ghanem; Osman, Ossama T.
Abstract : We report a case of a 34-year-old male who presented with an acute onset of pleomorphic psychiatric features. Upon examination we later diagnosed him with Gorlin-Goltz syndrome based on clinical and radiological findings that are characteristic for this rare autosomal dominant syndrome. His psychiatric manifestations included irritability, aggressive behavior, labile mood, hallucinations, paranoid delusions, and transient cognitive impairment. His past history indicated surgical excision of pigmented lesion in the left lower eyelid which turned out to be a basal cell carcinoma. His past visits to dermatology clinics indicated pitted keratosis involving hands, callosities, and seborrheic dermatitis. There were numerous palmar pits, and Brain CT Head scan revealed extensive calcification along falx cerebri and around the cerebellar vermis. He had low (20 ng/L) vitamin D level and high parathyroid hormone level. The patient improved using antipsychotic medications and vitamin D supplementations for symptomatic management and was discharged with a plan for multispecialty outpatient follow-up. This case highlights the importance of considering rare organic etiologies in the differential diagnosis of patients presenting with psychiatric symptoms. This is of vital importance for early intervention to prevent complications and for better outcomes of the coexistent diseases.